Scholarship of Syekh Jamaluddin Al-Qasimi (1282 H-1332 H) In Education - Harahap, Mhd. Harmidi; Tengku Kasim, Tengku Sarina Aini; Yussuf, Ahmad (Journal Analytica Islamica, 2024)
Education is an important thing in Islam. Every Muslim is encouraged to seek various types of knowledge. The importance of this education is clearly stated in the Qur’an and Sunnah and explained by Islamic scholars in their great works.This paper reveals the involvement and commitment of Sheikh Jamaluddin al-Qasimi in the field of education. He was a great contemporary scholar in Syria who produced several works discussing educational ideas. This paper focuses on his involvement in the field of education which includes an analysis of his students and his students and his educational works. This debate further examines his contributions and works in the field of education. The results of the study found that al-Qasimi has contributed a lot in the field of moral education, morality to oneself, morality to Allah SWT and his massanger, morality in the home and social society. Pendidikan merupakan perkara yang penting dalam Islam. Setiap Muslim digalakkan untuk menuntut pelbagai jenis ilmu. Kepentingan pendidikan ini secara jelas dinyatakan dalam al-Quran dan al-Sunnah serta dijelaskan oleh para sarjana Islam menerusi karya-karya agung mereka. Makalah ini menyingkap penglibatan dan komitmen Syekh Jamaluddin al-Qasimi dalam bidang pendidikan. Beliau merupakan ulama besar kontemporari di Syam yang menghasilkan beberapa karya yang membincangkan idea-idea pendidikan. Makalah ini menumpukan kepada penglibatan beliau dalam bidang pendidikan yang merangkumi analisis mengenai para murid dan karya-karya pendidikan beliau. Perbahasan ini seterusnya mengkaji sumbangan dan karya-karya beliau dalam bidang pendidikan. Hasil kajian mendapati bahawa al-Qasimi telah banyak memberikan sumbangan dalam bidang pendidikan akhlak, akhlak kepada diri sendiri, akhlak kepada Allah SWT dan RasulNya, akhlak di dalam rumah dan sosial kemasyarakatan